A formação de líderes segundo a ontopsicologia - Montenegro, Ana Claudia Valentini (2012)
Leadership has been in vogue nowadays, the features of a lider and their importance in order to the social and organizational context, however, in way to seek studies on the formation of leaders, very little is found and how states Banyai (2009), there is little agreement about what in fact it is leadership and how to do it. Kegan and Lahey (2009) argue that leadership development should be more focused on personal development process of a leader rather than the teaching of knowledge and skills associated with leadership. Despite it, there are not too much knowledge in the field of management training that focuses on the leader's personal,there are a vast field to be searched. Thus, the present study had the objective to analyze how is the training of young leaders under the Ontopsychology Methodology and what results this training provides to leaders. The Ontopsychology Methodology aims the holistic formation of individuals and uses own techniques and tools, based on their specific discovering for the training of young people who will be future business leaders. To Meneghetti (2008), the leader is one by his own selfishness, it means, to hold and build the best for yourself, also conducts the public interest, social, stimulates society, revitalizes and imposes a dialectic of growth and progress. It is a creative in the sense that realizes evolution and future functionality, is able to propose new models of society, solutions, perspectives. The research was performed with 9 young people between 25 and 30 years in different stages of formation; with 2 leaders who performs in companies where young people works and also have been formed since young by the Ontopsychology Methodology, and with 4 business leaders also formed based on Ontopsychology Methodology, but on their own business. The 4 young people working in companies located in the International Project of Art an Humanistic Culture Recanto Maestro RS, district recognized by the United Nations (UN) in 2007 as a project model to be followed for the reach of the 8 Millennium Development Goals.This study reinforced the idea that the individual must know about himself, learn to manage him before the individual learns to manage the function itself, the organization. In this way, the administrator, the professional who does not build himself, does not know how to do things well for him, does not know for the company, and to another. The use of the Ontopsychology methodology, as revealed by the research, enables the individual self process, which reflects not only results in personal life, but also in professional life and in the company directly.